HUBUNGAN PENDIDIKAN DENGAN PENGETAHUAN WANITA USIA SUBUR TENTANG PAP SMEAR DI PONDOK PESANTREN AL HIDAYAH KENDAL NGAWI - Martining Wardani, Erika MartiningWardani; Setiyowati, Eppy (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
Cervical cancer affected by Human Papilloma Virus (HPV) as highly women death cause cancer. It detectable early with pap smear examination. The high rate incidence of cervical cancer caused by lack of knowledge and awareness on the impact of cervical cancer. The lower knowledge level is believed aggravate condition and estimated will increase the incidence of cervical cancer. The objective of this research to recognize correlation of education level and knowledge on pap smear. This research was analytical research Rank Spearman with cross sectional method get α < 0,05. Sampling done using accidental sampling that were eligible women who undertaking pap smear examination as 36 respondents. The result of this research showed that 19,4% respondents get high school education and has adequate knowledge about pap smear as 52,8 with statistic test indicate there was correlation among education level (rValue = 0,000 < α) and pap smear knowledge. The higher education the better way to accept the information then many information gained. Well knowledge belong to eligible women gained through social interaction by sharing experiences with them who ever have pap smear. Well perception on cervical cancer correlated to early precaution of cervical cancer with pap smear.